Microsimulation projection of the educational integration and labour force participation of first- and second-generation immigrants - Gerard Thomas Horvath; Martin Spielauer; Marian Fink (Austrian Institute of Economic Research (WIFO), 2020)
In this paper, we present the results of a dynamic microsimulation analysis that examines how changes in the educational integration of first- and second-generation immigrants would affect the future size of the Austrian labour force. Due to population ageing and migration, the number and proportion of people with a migration background will increase significantly in the coming decades. Differences in educational careers, as well as differences in labour market participation between the second generation of migrants with EU or EFTA backgrounds and people without a migration background, would have only a minor impact on future labour force participation dynamics. In contrast, closing education and labour force participation gaps for the second generation of migrants with a third country background would lead to a significant increase in the size and qualification structure of the working population.
Keywords: I26; J15; O15; 330; Integration; Migration; Education; Human Capital; Dynamic microsimulation